PREVENTION AND MANAGEMENT OF GUDAGATA VIKARA (ANORECTAL DISORDERS)- AYURVEDIC PERSPECTIVE - Borkar Sneha P; Dongre Amol A (AYUSHDHARA, 2020)
Gudagata Vikara (Anorectal disorders) refers to ailments of the anus and/ or rectum. Gudagata Vikara includes; Arsha (Haemorrhoids), Bhagandara (Fistula in Ano), Parikartika (Fissure in Ano), Guda Kandu (Pruritus Ani), etc. These are some common disorders in human being. A study by Sharma et al. showed that Hemorrhoids (49%) and fistula-in-ano (27%) were commonest anorectal conditions, mostly affecting the age group 18-45 years. Apathya Ahara and Vihara leads to vitiation of Doshas causing Mandagni and vitiation of Apanavayu resulting in stagnation of Mala in Gudavali which leads to anorectal disorders. In present study a thorough and scientific review of Ahara (diet) and Vihara (lifestyle) has been carried out for the prevention and management of anorectal diseases. Materials and methods: Ayurvedic treaties, text books, Dissertation, Articles from PUBMED, SCOPUS, Google scholar, Mesh, Google search has been searched thoroughly related to the subject. Discussion: Gudagata Vikara, Anorectal Disorders, Ahara (Diet), Vihara (Lifestyle), Dinacharya, Ritucharya, Sadvritta has been discussed. Conclusions: Food articles mentioned in Ayurvedic text are effective in the management of Anorectal diseases. Lifestyle changes according to Dinacharya, Ritucharya and Sadavritta and following do’s and don’ts are effective in the management of Anorectal diseases